1999
DOI: 10.1097/00004647-199906000-00007
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Role for Erythropoietin in Focal Permanent Cerebral Ischemia in Mice

Abstract: The present study describes, for the first time, a temporal and spatial cellular expression of erythropoietin (Epo) and Epo receptor (Epo-R) with the evolution of a cerebral infarct after focal permanent ischemia in mice. In addition to a basal expression of Epo in neurons and astrocytes, a postischemic Epo expression has been localized specifically to endothelial cells (1 day), microglia/macrophage-like cells (3 days), and reactive astrocytes (7 days after occlusion). Under these conditions, the Epo-R express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
560
2
18

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 676 publications
(607 citation statements)
references
References 36 publications
27
560
2
18
Order By: Relevance
“…14 Several intracellular signal transduction cascades are involved in the antiapoptotic effects of Epo on erythroblasts including Ras-mitogen-activated protein kinase (MAPK), phosphatidylinositol 3-kinase (PI3-K), and the Bcl-2 family. 14,15 It is becoming increasingly clear that Epo has additional neuroprotective effects in different in vivo models of brain injury, [16][17][18][19] modulating the same signal transduction cascades that we identified to be involved in RGC death in our MOG-EAE model, the Bcl-2 family and the PI3-K/Akt pathway. 10 Furthermore, Epo has been demonstrated to delay the onset and to reduce the severity of clinical symptoms in an EAE model induced by myelin basic protein (MBP).…”
Section: Introductionmentioning
confidence: 85%
“…14 Several intracellular signal transduction cascades are involved in the antiapoptotic effects of Epo on erythroblasts including Ras-mitogen-activated protein kinase (MAPK), phosphatidylinositol 3-kinase (PI3-K), and the Bcl-2 family. 14,15 It is becoming increasingly clear that Epo has additional neuroprotective effects in different in vivo models of brain injury, [16][17][18][19] modulating the same signal transduction cascades that we identified to be involved in RGC death in our MOG-EAE model, the Bcl-2 family and the PI3-K/Akt pathway. 10 Furthermore, Epo has been demonstrated to delay the onset and to reduce the severity of clinical symptoms in an EAE model induced by myelin basic protein (MBP).…”
Section: Introductionmentioning
confidence: 85%
“…These actions are known to involve several receptors and signaling pathways. Many studies suggest a role of EPOR in tissue protection (Bernaudin et al, 1999;Siren et al, 2001), but the receptor complex mediating EPO hematopoietic effects and EPO neuroprotective actions differs in the affinity for EPO and the associated proteins involved (Masuda et al, 1993). Moreover, CEPO does not seem to bind to the EPOR despite displaying neuroprotective actions (Leist et al, 2004), but Brines et al (2004) recently reported that using knock out (KO) mice for the βcR subunit the neuroprotective effects of both EPO and CEPO were abolished.…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, EPO is highly expressed in development (Buemi et al, 2002;Nagai et al, 2001). In the mature brain, expression of EPO appears to be upregulated by oxidative or nitrosative stress (Bernaudin et al, 1999(Bernaudin et al, , 2000Chong et al, 2003;Digicaylioglu et al, 1995). Within the brain, functional EPORs are expressed by different cell types such as neurons, glial cells and brain capillary endothelial cells (Genc et al, 2004a,b), while the main source of EPO within the CNS itself appears to be the astroglial cells (Bernaudin et al, 2000;Digicaylioglu et al, 1995;Juul et al, 1998;Marti et al, 1996;Masuda et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, apart from its principal function in erythropoiesis, nonhematopoietic functions of EPO such as angiogenic, cardioprotective, and neuroprotective effects have attracted extensive concerned (Kertesz, Wu, Chen, Sucov, & Wu, 2004; Kumral et al., 2011; Tada et al., 2006). Erythropoietin receptor (EPOR) is expressed by a variety of nonhematopoietic cell types such as vascular smooth muscle cells, myocardial cells, brain capillary endothelial cells, and neurons (Acheson, Richards, & de Wit, 2007; Bernaudin et al., 1999; Cianferotti & Brandi, 2014; Wright et al., 2004). EPO can alleviate motor and cognitive deficit, axonal pathology, and neuroinflammation in the models of cerebral ischemia (Villa et al., 2003), experimental autoimmune encephalomyelitis (EAE) (Yuan et al., 2008), and diffuse axonal injury (DAI) (Hellewell, Yan, Alwis, Bye, & Morganti‐Kossmann, 2013).…”
Section: Introductionmentioning
confidence: 99%